Respostas funcionais das assembleias de peixes de riachos intermitentes aos distúrbios hidrológicos naturais - Santos, Ana Márcia Pinto dos (2021)
Natural disturbances such as river floods and droughts are directly and indirectly related to the assembly of biological communities, as these events can promote both the loss and the establishment of new species. Organisms can show different responses to these disturbances and the evaluation of these responses through functional diversity has been widely used in recent years. This study was carried out with the objective of to evaluate the functional response of fish assemblages to natural hydrological disturbances (flood and drought) in intermittent streams. Morphological measures were used to calculate the indices of Functional Richness (FRic), Functional Evenness (FEve), Functional Specialization (FSpe) and Functional Originality (FOri). Only FORi showed a significant difference between the hydrological phases, being higher (less redundant assemblies) in the dry phase (t= - 4.74, p<0.05). The functional attributes that most contributed to the separation of species in the flood phase were related to the form of food acquisition (relative mouth opening, eye size and length of gill raker), and in the dry phase the attributes that most contributed to species separation were related to locomotion and feeding (e.g. mouth opening, transverse body surface, relative height of the caudal peduncle). Biotic filtering may have been an important factor for the lower redundancy in the dry phase, leading species to use their attributes in a more unique way to be able to coexist. Furthermore, the type of sampling and the time scale used here may not have been sufficient to reflect changes in the functional structure. Studies like this one with a functional approach in intermittent streams, mainly focusing on functional redundancy, are still emerging, but understanding how biotic communities respond to disturbances is essential to support environmental management and planning considering future scenarios of climate change and expansion of the distribution of these ecosystems.